"Doing Explicit" in hospitality and tourism service encounters in English as a lingua franca. (April 2023) - Thongphut, Aonrumpa; Kaur, Jagdish
Abstract: In many highly heterogenous hospitality and tourism (HT) settings around the world, English is used to mediate hospitality service encounters. However, little is known about how front-desk staff are able to effectively communicate with international guests of diverse linguacultural backgrounds to deliver quality service. This study investigates the use of communications strategies by Thai front-desk staff that is characterized by increased explicitness in their interactions in English as a lingua franca (ELF) with international tourists. The data comprise 15 h of authentic interactions recorded at three sites: a tour service counter, an airport information counter, and a hotel front office. Using conversation analytic procedures, the analysis reveals the staff's orientation to explicitness: they repeat key information multiple times to increase its prominence, use explication, circumlocution, and self-reformulation to clarify keywords and repair ongoing utterances to address potential ambiguity. In the absence of overt displays of non/misunderstanding, the staff's use of multiple explicitness strategies in these short, routine exchanges points to explicitness as a defining feature of ELF HT service encounters. The findings of this study have implications for ESP course development in HT where awareness raising and practice in the use of explicitness strategies should be incorporated. Highlights: Staff in ELF hospitality service encounters do "being explicit". They self-repeat, clarify meaning, and self-repair to increase explicitness. The strategies are used in the absence of overt displays of non/misunderstanding. Multiple strategy-use points to explicitness as a defining feature of this setting.